High-durability super-amphiphobic aircraft anti-icing coating and preparation method thereof

By using modified core-shell structure micro-nanoparticles and fluorinated modified adhesives in aircraft anti-ice coatings, the existing coatings have been solved, and the problems of poor oil resistance, complex preparation and poor durability are achieved, and high durability and ultra-high Aircraft anti-ice coating with double-sparking performance and good protection effect.

CN119432210APending Publication Date: 2025-02-14CIVIL AVIATION FLIGHT UNIV OF CHINA

Patent Information

Application Number
CN202411719913.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing aircraft superhydrophobic anti-ice coatings have problems such as poor oil resistance, complex preparation process and poor durability, which leads to poor results in practical applications.

Method used

Modified core-shell structure micro-nanometers are prepared by using mixed alcohol solutions and microparticles as the basis, and modified silica nanoparticles and low-surface energy fluorosilanes, combined with fluorination modification of aqueous polyurethane adhesives by fluorinating fluorinated fluorinated polyurethane adhesives. The particles are mixed with modified polyurethane adhesive, sprayed onto the surface of the aircraft paint, and cured to produce a high-durability ultra-double-sparing aircraft anti-ice coating.

Benefits of technology

The coating is achieved with excellent repulsion of liquids with different surface tensions such as water, rapeseed oil, lubricating oil, etc., delays the freezing time of the droplets, and has a good comprehensive resistance to wear, airflow shock, oil stains, and acid and alkali corrosion. Protective performance, long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432210A_ABST
    Figure CN119432210A_ABST
Patent Text Reader

Abstract

The invention provides a high-durability super-amphiphobic aircraft anti-icing coating and a preparation method thereof.The preparation method comprises the steps that silicon dioxide nanoparticles are loaded on the surfaces of micron attapulgite particles in situ to prepare core-shell structure micro-nano composite particles, and low-surface-energy fluorosilane is added for modification; meanwhile, fluorinated modification is conducted on a waterborne polyurethane adhesive through fluorosilane, the modified micro-nano particles are introduced into the modified polyurethane adhesive, then the surface of semi-cured airplane paint is evenly sprayed with the modified polyurethane adhesive, and the super-amphiphobic anti-icing coating is prepared through curing. The super-double hydrophobic surface prepared by the method shows excellent repellency to liquids (water, rapeseed oil, lubricating oil and hexadecane) with different surface tensions, can delay icing of liquid drops on the surface of a coating for 440 seconds at-15 DEG C, and has excellent comprehensive protection performance of wear resistance, airflow impact resistance, oil stain resistance and acid and alkali corrosion resistance; good super-amphiphobic performance can be kept after mechanical wear and chemical corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of super-amphiphobic anti-icing coatings, and in particular to a highly durable super-amphiphobic aircraft anti-icing coating and a preparation method thereof. Background Art

[0002] When an aircraft flies in a high-altitude, low-temperature and high-humidity environment, it is easy for ice to form on the aircraft surface, wings, engine air intakes and other parts. These ice layers will increase the weight of the aircraft, change the aerodynamic characteristics, and affect the aircraft's control and performance. Perfect and efficient anti-icing measures are key components to ensure flight safety. Inspired by lotus leaves, super-hydrophobic surfaces are widely considered to be ideal anti-icing surfaces because of their excellent properties such as rapid water removal, delayed ice formation, and low ice adhesion. However, if the coating is washed by raindrops for a long time, oil stains will adhere to the surface of the coating, causing its super-hydrophobic properties to fail, and then lose the effect of rapid water removal. Therefore, when raindrops on the surface freeze, the micro-nanostructure of the super-hydrophobic surface locks with the ice, resulting in a significant increase in the adhesion of the ice. In addition, the complex coating preparation process and poor durability limit its practical application.

[0003] In summary, the existing aircraft super-hydrophobic anti-icing coatings have the following shortcomings: poor oil resistance, easy to be attached by oil stains; complex preparation process; poor durability. Summary of the invention

[0004] To solve the above problems, the purpose of the present invention is to provide an aircraft anti-icing coating with high durability and both super hydrophobic and super oleophobic properties and a preparation method thereof. The coating has a simple preparation process, is convenient for large-scale application, has good durability and resistance to oil and dirt adhesion, and has a long service life.

[0005] The present invention provides a method for preparing a highly durable super-amphiphobic aircraft anti-icing coating, which specifically comprises the following steps:

[0006] (1) preparing an alcohol mixed solution: slowly dropping a certain amount of an acidic or alkaline aqueous solution into an alcohol solvent to obtain an alcohol mixed solution having a certain pH value;

[0007] (2) preparing core-shell structured micro-nano particles: adding an appropriate amount of micron particles to the alcohol mixed solution obtained in step (1), stirring evenly to obtain a micron particle dispersion, wherein the mass fraction of the micron particles in the micron particle dispersion is 2%-4%, then slowly dropping tetraethyl orthosilicate into the dispersion, stirring to react, after the stirring is completed, centrifuging the obtained solution, discarding the upper layer of liquid, and centrifuging the obtained precipitate to wash and dry to obtain core-shell structured micro-nano particles;

[0008] (3) Preparing modified core-shell structured micro-nano particles: preparing another alcohol mixed solution according to the method of step (1), dispersing the core-shell structured micro-nano particles obtained in step (2) in the alcohol mixed solution, adding modified fluorosilane dropwise to the mixed solution, stirring continuously, centrifuging the obtained solution after stirring, discarding the upper liquid, centrifuging the obtained precipitate, washing and drying it, and crushing, grinding and sieving it after drying to obtain modified core-shell structured micro-nano particles;

[0009] (4) Preparing a modified adhesive: dropping the adhesive into an ethylene glycol solution and stirring evenly to obtain a solution A; preparing a third alcohol mixed solution according to the method of step (1); slowly dropping the modified fluorosilane into the alcohol mixed solution; then dropping a small amount of tetraethyl orthosilicate and continuously stirring at room temperature to obtain a solution B; mixing solution A and solution B and continuously stirring to obtain a modified polyurethane adhesive;

[0010] (5) The modified core-shell structured micro-nanoparticles obtained in step (3) and the modified adhesive obtained in step (4) are mixed in a certain proportion, stirred evenly, to obtain a super-amphiphobic coating, and the super-amphiphobic coating is sprayed on the surface of aircraft paint. After curing, a highly durable super-amphiphobic aircraft anti-icing coating is obtained.

[0011] Furthermore, in step (1), the acidic aqueous solution is one of hydrochloric acid, nitric acid, and acetic acid aqueous solutions, and the alkaline aqueous solution is one of ammonia water, sodium hydroxide, and potassium hydroxide aqueous solutions.

[0012] Furthermore, in step (1), if an acidic aqueous solution is added, the pH value of the alcohol mixed solution is 2-4; if an alkaline aqueous solution is added, the pH value of the alcohol mixed solution is 8-12.

[0013] Furthermore, the micron particles in step (2) are micron-sized attapulgite particles, and the particle size thereof is less than 38 μm.

[0014] Furthermore, in step (2), the molar ratio of tetraethyl orthosilicate to micron attapulgite is (5-8):1.

[0015] Furthermore, in step (2), after adding tetraethyl orthosilicate, the stirring time is not less than 2 hours, and the stirring temperature is 40-50°C.

[0016] Furthermore, the modified fluorosilane in step (3) is at least one of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane or triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane, and the molar ratio of the modified fluorosilane added in step (3) to the micron attapulgite in step (2) is (0.8-2.2):1.

[0017] Furthermore, in step (3), in order to ensure the removal of unreacted fluorosilane on the particle surface, the drying temperature is controlled at 100-120°C.

[0018] Furthermore, in step (3), after adding the modified fluorosilane, the stirring time is not less than 2 hours, and the stirring temperature is 40-50°C.

[0019] Furthermore, in steps (2) and (3), the centrifugal speed is 1500-3500 r / min, the centrifugal time is 5-10 min, and the washing is performed using deionized water and anhydrous ethanol respectively, and the number of washing times is not less than 5 times.

[0020] Furthermore, the modified fluorosilane in step (4) is at least one of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane or triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane.

[0021] Furthermore, the adhesive in step (4) is a water-based polyurethane adhesive.

[0022] Furthermore, in step (4), the volume ratio of the modified fluorosilane to tetraethyl orthosilicate is 10:1, wherein the role of tetraethyl orthosilicate is to promote the hydrolysis of the modified fluorosilane.

[0023] Furthermore, when preparing solution B in step (4), the stirring time at room temperature is not less than 2 hours.

[0024] Furthermore, in step (4), the mass ratio of the adhesive to the modified fluorosilane is 1:0.2-0.4.

[0025] Furthermore, in step (4), the stirring time after mixing solution A and solution B is no less than 30 minutes.

[0026] Furthermore, in step (5), the mass ratio of the modified core-shell structured micro-nano particles to the modified adhesive is 1:(0.4-0.8).

[0027] Furthermore, the nozzle diameter of the spray gun used for spraying in step (5) is 0.8-1.5 mm, the spraying pressure is 0.6 MPa, and the distance is 25-30 cm.

[0028] Furthermore, in step (5), the aircraft paint surface is made of zinc yellow acrylic polyurethane primer and polyurethane matte enamel for aircraft skin, and the aircraft paint surface is a semi-cured surface.

[0029] Furthermore, in step (5), the coating is cured at 50° C. for 48 hours.

[0030] The present invention also provides a highly durable super-amphiphobic aircraft anti-icing coating obtained according to the above preparation method.

[0031] Furthermore, the highly durable super-amphiphobic aircraft anti-icing coating has a static contact angle greater than 150° and a rolling angle less than 10° for liquids with different surface tensions (including water, rapeseed oil, lubricating oil, and hexadecane). At -15°C, the coating surface can delay the freezing time of droplets by up to 440 seconds. In addition, the coating can resist a variety of mechanical and chemical damage.

[0032] The present invention proposes a highly durable super-amphiphobic aircraft anti-icing coating and a preparation method thereof, the preparation method comprising in-situ loading of silica nanoparticles on the surface of micronized attapulgite particles, and modifying them with low surface energy fluorosilane, and at the same time using fluorosilane to fluorinate the waterborne polyurethane adhesive, and introducing the modified core-shell structured micro-nanoparticles into the modified polyurethane adhesive, and then uniformly spraying it onto the surface of the aircraft paint, and curing to obtain a super-amphiphobic anti-icing coating. The super-hydrophobic surface prepared by this method exhibits excellent repellency to liquids with different surface tensions such as water, rapeseed oil, lubricating oil, and hexadecane, and can delay the freezing of droplets on the coating surface for 440 seconds at -15°C, and has excellent comprehensive protective properties of wear resistance, airflow impact resistance, oil pollution resistance, and acid and alkali corrosion resistance, and can maintain good super-amphiphobic and self-cleaning properties after mechanical wear and chemical corrosion.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The preparation process of the present invention is short, the operation is convenient and safe, the equipment is simple, the cost is low, and it is suitable for large-scale preparation and application;

[0035] (2) The present invention adopts the method of in-situ loading and fluorosilane modification to prepare modified core-shell structured micro-nano composite particles, which reduces the surface tension and super-amphiphobic properties of the particles, is conducive to constructing a micro / nano hierarchical structure on the coating surface, and improves the lyophobic properties of the coating;

[0036] (3) The aircraft paint binder used in the present invention is the same as the coating binder, which can provide a good attachment site for coating deposition, increase the adhesion between the aircraft paint and the coating, make the coating adhere more firmly during the curing process, and enhance the durability of the coating;

[0037] (4) The super-amphiphobic coating prepared by the present invention has a micro-nano hierarchical structure surface, which provides excellent droplet repellency, and the air between the micro-nano structure and the droplets can serve as a thermal barrier layer to slow down the heat exchange between the droplets and the surface, delaying the freezing time of the droplets by up to 440 seconds;

[0038] (5) The super-amphiphobic coating prepared by the present invention still maintains good super-amphiphobic properties after being subjected to sandpaper abrasion, high-speed airflow impact, acid-base salt solution immersion, high temperature and high humidity treatment, etc.

[0039] (6) The present invention can obtain a stable super-amphiphobic coating after deposition and curing by spraying, which is beneficial for large-area overall construction, especially for the processing of parts with irregular shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 3. The morphology and performance characterization diagram of the highly durable super-amphiphobic aircraft anti-icing coating prepared in Example 1, wherein Figure a is an electron microscope image of the modified core-shell structured micro-nanoparticles obtained in step (3) of Example 1, and Figure b is a low-magnification electron microscope image of the highly durable super-amphiphobic aircraft anti-icing coating obtained in step (5) of Example 1, and Figure b also shows the wettability of the coating, and Figure c is a high-magnification electron microscope image of the highly durable super-amphiphobic aircraft anti-icing coating of the rectangular portion shown by the dotted line in Figure b, and Figure d is a test diagram of the oleophobic performance of the highly durable super-amphiphobic aircraft anti-icing coating, and Figure e is a test diagram of the anti-icing performance of the highly durable super-amphiphobic aircraft anti-icing coating;

[0041] Figure 2 It is a characterization graph of the durability performance of the high-durability super-amphiphobic aircraft anti-icing coating prepared in Example 1, wherein Figure a is a wettability graph of the coating after multiple wear cycles, Figure b is a wettability graph of the coating after being impacted by airflow (0.6MPa) for different times, Figure c is a wettability graph of the coating after being immersed in oil for different times, and Figure d is a wettability graph of the coating after being immersed in solutions with different pH values ​​for 2 hours. DETAILED DESCRIPTION

[0042] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples and accompanying drawings. The following examples are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following examples. The reagents or instruments used without indicating the manufacturer can all be purchased commercially.

[0043] Embodiment 1:

[0044] (1) adding 6 mL of 28% ammonia water dropwise into 50 mL of anhydrous ethanol, and stirring the mixture with a magnetic force at a speed of 400 r / min for 5 min to obtain an ethanol / ammonia water mixed solution, wherein the pH value of the ethanol / ammonia water mixed solution is about 11;

[0045] (2) Preparation of core-shell structured micro-nanoparticles: 1 g of micron-sized attapulgite particles (molecular weight 583.377 g / mol) with a particle size of less than 38 μm was added in batches to the ethanol / ammonia mixed solution obtained in step (1), and magnetically stirred for 30 min to completely disperse the particles to obtain a micron particle dispersion, and then 3 mL of tetraethyl orthosilicate was slowly added dropwise to the micron particle dispersion, and magnetically stirred at 40° C. for 4 h to ensure that the tetraethyl orthosilicate was completely hydrolyzed and loaded onto the surface of the attapulgite. After stirring, the obtained solution was centrifuged at a speed of 3000 r / min for 5 min, the upper layer of liquid was discarded, and the obtained precipitate was centrifuged and washed 5 times with deionized water and ethanol respectively to remove excess silica sol, and then dried at 120° C. to obtain core-shell structured micro-nanoparticles;

[0046] (3) Preparing modified core-shell structured micro-nanoparticles: another portion of ethanol / ammonia water mixed solution is prepared by the method in step (1), the core-shell structured micro-nanoparticles prepared in step (2) are dispersed in the ethanol / ammonia water mixed solution, and 1 mL of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is added dropwise to the solution, and magnetic stirring is performed at 40° C. for 6 h to induce hydrolysis and condensation of fluorosilane; after the stirring is completed, the obtained solution is centrifuged at a speed of 3000 r / min for 5 min, the upper layer of liquid is discarded, and the obtained precipitate is centrifuged and washed 5 times with deionized water and ethanol respectively until the supernatant becomes completely neutral, and the obtained precipitate is dried at 120° C. for 8 h. After the drying is completed, it is crushed and ground and passed through a 50-mesh sieve to obtain fluorosilane-modified micro-nanoparticles, i.e., modified core-shell structured micro-nanoparticles;

[0047] (4) Preparation of fluorosilane modified adhesive: 0.8 g of waterborne polyurethane adhesive was added dropwise to 5 mL of ethylene glycol, and magnetically stirred at 400 r / min for 2 h at room temperature to obtain solution A; according to the method of step (1), 20 mL of ethanol / ammonia mixed solution was prepared, specifically, 2.1 mL of 28% ammonia water was added dropwise to 17.9 mL of anhydrous ethanol, and magnetically stirred at 400 r / min for 5 min; 0.2 mL of 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane was added dropwise to 0.2 mL of 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane; Alkane is slowly added dropwise to the 20 mL ethanol / ammonia mixed solution, and then 0.02 mL tetraethyl orthosilicate is added dropwise to promote the hydrolysis of the modified fluorosilane, and the mixture is continuously stirred at room temperature for 2 h to obtain solution B; solution A is mixed with solution B, and the mixture is continuously stirred at a speed of 400 r / min for 6 h to make the reaction uniform, and a modified polyurethane adhesive solution is obtained after the stirring is completed, and the modified polyurethane adhesive solution is placed in a 40° C. thermostat and heated for 1 h to evaporate the excess solvent in the volatile solution, and a modified polyurethane adhesive is obtained after the heating is completed;

[0048] (5) The fluorosilane-modified micro-nanoparticles prepared in step (3) and the modified polyurethane adhesive prepared in step (4) are mixed in a mass ratio of 1:0.6, and magnetically stirred for 30 minutes to obtain a super-amphiphobic coating. The super-amphiphobic coating is sprayed on the surface of the semi-cured aircraft paint. The spray gun nozzle diameter used for spraying is 1.5 mm, the spraying pressure is 0.6 MPa, and the distance is 25 cm. After the spraying is completed, it is cured at 50° C. for 48 hours to obtain a highly durable super-amphiphobic aircraft anti-icing coating.

[0049] Wherein, the semi-cured aircraft paint surface in step (5) is obtained by the following steps: the aluminum alloy substrate is polished with 600#, 1000#, and 2000# SiC sandpaper in sequence, and then ultrasonically cleaned in acetone and ethanol to remove surface oil stains. After the ultrasonic treatment, the aluminum alloy substrate is taken out and rinsed with deionized water and placed in an oven for drying. After the drying, it is anodized. The anodizing treatment belongs to the prior art and will not be repeated here. The aircraft-specific zinc yellow acrylic polyurethane primer is diluted with a special diluent for lighthouse TSX-70 aircraft paint at a mass ratio of 1:2, and after ripening for 0.5h, it is sprayed on the surface of the anodized aluminum alloy substrate and dried at room temperature for 24h. The aircraft skin polyurethane matte magnetic paint is diluted with a special diluent for lighthouse TSX-70 aircraft paint at a mass ratio of 1:2 and ripened, and then sprayed on the surface of the semi-cured primer, and dried at 50°C for 24h to obtain a semi-cured aircraft paint surface.

[0050] The high-durability super-amphiphobic aircraft anti-icing coating prepared in Example 1 was subjected to durability test according to the following method:

[0051] Sandpaper wear: The super-amphiphobic coating with a load of 4.1 kPa was rubbed on 1000-mesh sandpaper for 120 cycles, and each reciprocating friction total length of 30 cm was defined as one cycle.

[0052] Airflow impact: Use high-pressure airflow from a spray gun to impact the surface of the sample at a distance of 10 cm from the coating, and the airflow pressure is 0.6 MPa.

[0053] Oil immersion pollution: immerse the coating directly in lubricating oil and observe the change of the amphiphobicity with immersion time.

[0054] Acid and alkali corrosion: Soak the coating in solutions with different pH values ​​for 2 hours (the pH value of the solution is adjusted by dilute hydrochloric acid and sodium hydroxide solution).

[0055] The electron microscope image of the fluorosilane-modified micro-nano particles obtained in step (3) of Example 1 is as follows: Figure 1 As shown in Figure a, the low-power electron microscope image of the highly durable super-amphiphobic aircraft anti-icing coating prepared in step (5) is as follows: Figure 1As shown in Figure b, Figure b also shows the wettability of the high-durability super-amphiphobic aircraft anti-icing coating, Figure c is a high-magnification electron microscope image of the high-durability super-amphiphobic aircraft anti-icing coating in the rectangular part shown by the dotted line in Figure b, Figure d is a test diagram of the oil repellency of the high-durability super-amphiphobic aircraft anti-icing coating, and Figure e is a test diagram of the anti-icing performance of the high-durability super-amphiphobic aircraft anti-icing coating.

[0056] Figure 2 It is a characterization graph of the durability performance of the high-durability super-amphiphobic aircraft anti-icing coating prepared in Example 1, wherein Figure a is a wettability graph of the coating after multiple wear cycles, Figure b is a wettability graph of the coating after being impacted by airflow (0.6MPa) for different times, Figure c is a wettability graph of the coating after being immersed in oil for different times, and Figure d is a wettability graph of the coating after being immersed in solutions with different pH values ​​for 2 hours.

[0057] After testing, the highly durable super-amphiphobic aircraft anti-icing coating prepared in Example 1 has a static contact angle greater than 150° for liquids with different surface tensions (including water, rapeseed oil, lubricating oil, and hexadecane), and a rolling angle less than 10°. At -15°C, the coating surface can delay the freezing time of droplets up to 440s. In addition, the coating still maintains super-amphiphobic properties after undergoing a variety of mechanical and chemical damage tests (including sandpaper wear, airflow impact, oil immersion pollution, acid and alkali corrosion).

[0058] Embodiment 2:

[0059] (1) adding 15 mL of 0.05 M dilute hydrochloric acid dropwise to 75 mL of anhydrous ethanol, and stirring the mixture with a magnetic force at a speed of 400 r / min for 5 min to obtain an ethanol / hydrochloric acid mixed solution, wherein the pH value of the ethanol / hydrochloric acid mixed solution is about 2;

[0060] (2) Preparation of core-shell structured micro-nanoparticles: Subsequently, 1.5 g of micron-sized attapulgite particles (molecular weight 583.377 g / mol) with a particle size of less than 38 μm were added in batches to the ethanol / hydrochloric acid mixed solution prepared in step (1), and magnetically stirred for 30 min to completely disperse them to obtain a micron particle dispersion, and then 4.5 mL of tetraethyl orthosilicate was slowly added dropwise to the micron particle dispersion, and magnetically stirred at 40° C. for 4 h to ensure that the tetraethyl orthosilicate was completely hydrolyzed and loaded onto the surface of the attapulgite; after stirring, the obtained solution was centrifuged at a speed of 3000 r / min for 5 min, the upper layer of liquid was discarded, and the obtained precipitate was centrifuged and washed 5 times with deionized water and ethanol respectively to remove excess silica sol, and then dried at 120° C. to obtain core-shell structured micro-nanoparticles;

[0061] (3) Preparing modified core-shell structured micro-nanoparticles: another portion of ethanol / hydrochloric acid mixed solution is prepared by the method in step (1), the core-shell structured micro-nanoparticles prepared in step (2) are dispersed in the ethanol / hydrochloric acid mixed solution, and 1.5 mL of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is added dropwise to the solution, and magnetic stirring is performed at 40° C. for 6 h to induce hydrolysis and condensation of fluorosilane; after the stirring is completed, the obtained solution is centrifuged at a speed of 3000 r / min for 5 min, the upper layer of liquid is discarded, and the obtained precipitate is centrifuged and washed 5 times with deionized water and ethanol respectively until the supernatant becomes completely neutral, and the obtained precipitate is dried at 120° C. for 8 h. After the drying is completed, it is crushed and ground and passed through a 50-mesh sieve to obtain fluorosilane-modified micro-nanoparticles, i.e., modified core-shell structured micro-nanoparticles;

[0062] (4) Preparation of fluorosilane modified adhesive: 1.6 g of waterborne polyurethane adhesive was added dropwise to 10 mL of ethylene glycol, and magnetically stirred at 400 r / min for 2 h at room temperature to obtain solution A; according to the method of step (1), 40 mL of ethanol / hydrochloric acid mixed solution was prepared, wherein 40 mL of ethanol / hydrochloric acid mixed solution was obtained by adding 7.5 mL of 0.05 M dilute hydrochloric acid to 32.5 mL of anhydrous ethanol, and magnetically stirring at 400 r / min for 5 min; 0.4 mL of 1H, 1H, 2H, 2H-perfluoro Decyltriethoxysilane was slowly added dropwise to the above 40 mL ethanol / hydrochloric acid mixed solution, and then 0.04 mL tetraethyl orthosilicate was added dropwise to promote the hydrolysis of modified fluorosilane, and the mixture was continuously stirred at room temperature for 2 h to obtain solution B; solution A was mixed with solution B, and the mixture was continuously stirred at a speed of 400 r / min for 6 h to make the reaction uniform, and a modified polyurethane adhesive solution was obtained after the stirring was completed, and the modified polyurethane adhesive solution was placed in a 40° C. constant temperature box and heated for 1 h to evaporate the excess solvent in the volatile solution, and a modified polyurethane adhesive was obtained after the heating was completed;

[0063] (5) The fluorosilane-modified micro-nanoparticles prepared in step (3) and the modified polyurethane adhesive prepared in step (4) are mixed in a mass ratio of 1:0.5, and magnetically stirred for 30 minutes to obtain a super-amphiphobic coating. The super-amphiphobic coating is sprayed on the surface of the semi-cured aircraft paint. The spray gun nozzle diameter used for spraying is 1.5 mm, the spraying pressure is 0.6 MPa, and the distance is 25 cm. After the spraying is completed, it is cured at 50° C. for 48 hours to obtain a highly durable super-amphiphobic aircraft anti-icing coating.

[0064] Wherein, the preparation process of the semi-cured aircraft paint surface in step (5) is the same as that in Example 1.

[0065] Embodiment 3:

[0066] (1) adding 1.6 mL of 99.5% glacial acetic acid dropwise to 50 mL of anhydrous ethanol, and stirring the mixture with a magnetic force at a speed of 400 r / min for 5 min to obtain an ethanol / glacial acetic acid mixed solution, wherein the pH value of the ethanol / glacial acetic acid mixed solution is about 4;

[0067] (2) Preparation of core-shell structured micro-nanoparticles: 1 g of micron-sized attapulgite particles (molecular weight 583.377 g / mol) with a particle size of less than 38 μm was added in batches to the ethanol / glacial acetic acid mixed solution described in step (1), and magnetically stirred for 30 min to completely disperse the particles to obtain a micron particle dispersion, and then 2.5 mL of tetraethyl orthosilicate was slowly added dropwise to the micron particle dispersion, and magnetically stirred at 40° C. for 4 h to ensure that the tetraethyl orthosilicate was completely hydrolyzed and loaded onto the surface of the attapulgite; after stirring, the obtained solution was centrifuged at a speed of 3000 r / min for 5 min, the upper layer of liquid was discarded, and the obtained precipitate was centrifuged and washed 5 times with deionized water and ethanol respectively to remove excess silica sol, and then dried at 120° C. to obtain core-shell structured micro-nanoparticles;

[0068] (3) Preparing modified core-shell structured micro-nanoparticles: another ethanol / glacial acetic acid mixed solution is prepared by the method in step (1), and the core-shell structured micro-nanoparticles prepared in step (2) are dispersed in the ethanol / glacial acetic acid mixed solution, and then 1.5 mL of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is added dropwise to the solution, and magnetic stirring is performed at 40° C. for 6 h to induce hydrolysis and condensation of fluorosilane; after the stirring is completed, the obtained solution is centrifuged at a speed of 3000 r / min for 5 min, the upper liquid is discarded, and the obtained precipitate is centrifuged and washed with deionized water and ethanol for 5 times respectively until the supernatant becomes completely neutral, and the obtained precipitate is dried at 120° C. for 8 h. After the drying is completed, it is crushed and ground and passed through a 50-mesh sieve to obtain fluorosilane-modified micro-nanoparticles, i.e., modified core-shell structured micro-nanoparticles;

[0069] (4) Preparation of fluorosilane modified adhesive: 2 g of waterborne polyurethane adhesive was added dropwise to 10 mL of ethylene glycol, and magnetically stirred at 400 r / min for 2 h at room temperature to obtain solution A; according to the method of step (1), 40 mL of ethanol / glacial acetic acid mixed solution was prepared, wherein 40 mL of ethanol / glacial acetic acid mixed solution was specifically prepared by adding 1.24 mL of 0.05 M dilute hydrochloric acid to 38.76 mL of anhydrous ethanol, and magnetically stirring at 400 r / min for 5 min; 0.5 mL of 1H, 1H, 2H, 2H -Perfluorodecyltriethoxysilane was slowly added dropwise to the above 40 mL ethanol / hydrochloric acid mixed solution, and then 0.05 mL tetraethyl orthosilicate was added dropwise to promote the hydrolysis of the modified fluorosilane, and the mixture was stirred continuously for 2 h at room temperature to obtain solution B; solution A was mixed with solution B, and the mixture was stirred continuously for 6 h at a speed of 400 r / min to make the reaction uniform, and a modified polyurethane adhesive solution was obtained after the stirring was completed, and the modified polyurethane adhesive solution was placed in a 40° C. constant temperature box and heated for 1 h to evaporate the excess solvent in the volatile solution, and a modified polyurethane adhesive was obtained after the heating was completed;

[0070] (5) The fluorosilane-modified micro-nanoparticles prepared in step (3) and the modified polyurethane adhesive prepared in step (4) are mixed in a mass ratio of 1:0.7, and magnetically stirred for 30 minutes to obtain a super-amphiphobic coating. The super-amphiphobic coating is sprayed on the surface of the semi-cured aircraft paint. The spray gun nozzle diameter used for spraying is 1.5 mm, the spraying pressure is 0.6 MPa, and the distance is 25 cm. After the spraying is completed, it is cured at 50° C. for 48 hours to obtain a highly durable super-amphiphobic aircraft anti-icing coating.

[0071] Wherein, the preparation process of the semi-cured aircraft paint surface in step (5) is the same as that in Example 1.

[0072] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a highly durable super-amphiphobic aircraft anti-icing coating, characterized in that: The specific steps include: (1) preparing an alcohol mixed solution: slowly dropping a certain amount of an acidic or alkaline aqueous solution into an alcohol solvent to obtain an alcohol mixed solution having a certain pH value; (2) preparing core-shell structured micro-nano particles: adding an appropriate amount of micron particles to the alcohol mixed solution obtained in step (1), stirring evenly, to obtain a micron particle dispersion with a mass fraction of 2% to 4%, then slowly dropping tetraethyl orthosilicate into the dispersion, stirring to react, after the stirring is completed, centrifuging the obtained solution, discarding the upper layer of liquid, and centrifuging the obtained precipitate to wash and dry to obtain core-shell structured micro-nano particles; (3) Preparing modified core-shell structured micro-nano particles: preparing another alcohol mixed solution according to the method of step (1), dispersing the core-shell structured micro-nano particles obtained in step (2) in the alcohol mixed solution, adding modified fluorosilane dropwise to the mixed solution, stirring continuously, centrifuging the obtained solution after stirring, discarding the upper liquid, centrifuging the obtained precipitate, washing and drying it, and crushing, grinding and sieving it after drying to obtain modified core-shell structured micro-nano particles; (4) Preparing a modified adhesive: dropping the adhesive into an ethylene glycol solution and stirring evenly to obtain a solution A; preparing a third alcohol mixed solution according to the method of step (1); slowly dropping the modified fluorosilane into the alcohol mixed solution; then dropping a small amount of tetraethyl orthosilicate and continuously stirring at room temperature to obtain a solution B; mixing solution A and solution B and continuously stirring to obtain a modified polyurethane adhesive; (5) The modified core-shell structured micro-nanoparticles obtained in step (3) and the modified adhesive obtained in step (4) are mixed in a certain proportion, stirred evenly, to obtain a super-amphiphobic coating, and the super-amphiphobic coating is sprayed on the surface of aircraft paint. After curing, a highly durable super-amphiphobic aircraft anti-icing coating is obtained.

2. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: In step (1), the acidic aqueous solution is one of hydrochloric acid, nitric acid, and acetic acid aqueous solutions, and the alkaline aqueous solution is one of ammonia water, sodium hydroxide, and potassium hydroxide aqueous solutions; if the acidic aqueous solution is added, the pH value of the alcohol mixed solution is 2-4; if the alkaline aqueous solution is added, the pH value of the alcohol mixed solution is 8-12.

3. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: The micron particles in step (2) are micron-sized attapulgite particles with a particle size of less than 38 μm; the molar ratio of tetraethyl orthosilicate to micron attapulgite is (5-8):1; after adding tetraethyl orthosilicate, the stirring time is not less than 2 hours, and the stirring temperature is 40-50°C.

4. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: The modified fluorosilane in steps (3) and (4) is at least one of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane or triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane.

5. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: In step (3), the drying temperature is 100-120° C.; after adding the modified fluorosilane, the stirring time is not less than 2 hours, and the stirring temperature is 40-50° C.; the molar ratio of the modified fluorosilane added in step (3) to the micron attapulgite in step (2) is (0.8-2.2):

1.

6. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: In steps (2) and (3), the centrifugal speed is 1500-3500 r / min, the centrifugal time is 5-10 min, and the washing is performed using deionized water and anhydrous ethanol respectively, and the number of washing times is not less than 5 times.

7. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: In step (4), the adhesive is a water-based polyurethane adhesive, and the volume ratio of modified fluorosilane to tetraethyl orthosilicate is 10:1; when preparing solution B, the stirring time at room temperature is not less than 2 hours; the mass ratio of the adhesive to the modified fluorosilane is 1:0.2-0.4; and the stirring time after mixing solution A and solution B is not less than 30 minutes.

8. The method for preparing a highly durable super-amphiphobic aircraft anti-icing coating according to claim 1, characterized in that: In step (5), the mass ratio of the modified core-shell structured micro-nano particles to the modified adhesive is 1:(0.4-0.8); the diameter of the spray gun nozzle used for spraying is 0.8-1.5 mm, the spraying pressure is 0.6 MPa, and the distance is 25-30 cm; the aircraft paint surface is made of zinc yellow acrylic polyurethane primer and polyurethane matte varnish for aircraft skin, and the aircraft paint surface is a semi-cured surface; the coating curing conditions are 48 hours at 50° C.

9. A highly durable super-amphiphobic aircraft anti-icing coating obtained by the preparation method according to any one of claims 1 to 8.

10. The highly durable super-amphiphobic aircraft anti-icing coating according to claim 9, characterized in that: The static contact angles of the coating to water, rapeseed oil, lubricating oil and hexadecane are all greater than 150°, and the rolling angles are all less than 10°; at -15°C, the coating surface delays the freezing time of droplets by 440s.

Citation Information

Patent Citations

  • Airplane wing transition delay method based on micro-nano coating

    CN106189631A

  • Preparation method of super-amphiphobic coating capable of being sprayed and lastingly resisting icing

    CN107022291A

  • Aqueous wear-resistant super-hydrophobic and super-oleophobic nano composite coating and preparation method thereof

    CN111019447A

  • Preparation method of super-hydrophobic coating based on micro / nano inorganic particle synergistically reinforced fluorocarbon resin

    CN111138917A

  • Method for preparing stable super-hydrophobic surface on complex modeling base material at super-fast speed

    CN114773921A

Cited By

  • Polar region ship anti-icing coating capable of adjusting ice adhesive force and preparation method

    CN119912873A